POLA SEKSI URUSAN AGAMA ISLAM (URAIS) KANTOR URUSAN AGAMA KECAMATAN HATONDUHAN KABUPATEN SIMALUNGUN - Amrar Mahfuzh Faza (Jurnal At-Tabayyun, 2018)
In the life of the nation and state, there is a well-known Religion of Life Harmony Trilogy, which is a strategy of religious harmony in a democratic society, in order to avoid conflicts between religious adherents and the government. There are several factors supporting religious harmony, namely aspects of religious teachings, socio-cultural aspects, legal aspects, and historical aspects. The coaching paradigm in religious harmony is well-known in the New Order era which has meaning as a form of interfaith relations designed by the state, and carried out through the state bureaucracy from the center to the regions. According to Azyumardi, this was quoted by Sunardi that this kind of form was not initiated by the religious elite (especially by the people) but by the government, especially by the Ministry of Religion. On this basis the writer tries to see the importance of the Ministry of Religion's role in maintaining and maintaining the continuity of inter-religious harmony which is specifically applied by the Ministry of Religion of Hatonduhan District, Simalungun District in the Urais Section.